1997
DOI: 10.1109/38.626967
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Reality Gorilla Exhibit

Abstract: The Virtual Reality Gorilla Exhibit teaches users about gorilla behaviors and social interactions. We present techniques for building the environment and the virtual gorillas that inhabit it. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…However, when the designer has intentionally developed a VR system for enjoyment and education, positive subjective ratings of enjoyment abound (Allison et al 1997;Barab et al 2007;Bobick et al 1999;Dede et al 2005;Johnson et al 1999;Roussos et al 1999;Roussou et al 2006;Schell and Shochet 2001). This is the research space were the Virtual Trillium Trail resides.…”
Section: Overview Of Virtual Reality Research and Educationmentioning
confidence: 93%
“…However, when the designer has intentionally developed a VR system for enjoyment and education, positive subjective ratings of enjoyment abound (Allison et al 1997;Barab et al 2007;Bobick et al 1999;Dede et al 2005;Johnson et al 1999;Roussos et al 1999;Roussou et al 2006;Schell and Shochet 2001). This is the research space were the Virtual Trillium Trail resides.…”
Section: Overview Of Virtual Reality Research and Educationmentioning
confidence: 93%
“…To explain these bene"ts it has been suggested that one of the key properties of virtual environments is their ability to captivate: for example, Bricken and Byrne (1993) suggest that immersion in 3D environments is highly motivating, inducing users to spend more time on a given activity. Similarly, Allison, Wills, Bowman, Wineman and Hodges (1997) found that in their virtual gorilla project, users were highly engaged and very much enjoyed the experience (the users adopt the role of a gorilla in a virtual zoo, navigating the environment and watching other virtual gorillas respond to their presence).…”
Section: Introductionmentioning
confidence: 94%
“…The value of 3D interactivity has been supported by much prior research. For example, effective 3D interaction has been found to improve task performance by an order of magnitude over conventional 2D input for some scientific visualization tasks (van Dam, Forsberg, Laidlaw, LaViola, & Simpson, 2000); interactivity is also claimed to provide better spatial understanding for training and modeling, and to improve the user experience (Allison, Wills, Bowman, Wineman, & Hodges, 1997).…”
Section: Related Workmentioning
confidence: 99%